21st century communication : a reference handbook - Eadie, William F. (Thousand Oaks, California : Sage Publications, 2009)
Capturing all the major themes and subfields within communication this set covers approaches to the study of communication, key processes, forms and types, key characteristics of messages, key communication relationships, factors affecting communication, and challenges and opportunities.
"A Sage reference publication."
Includes bibliographical references and index
Keywords: Communication; Mass media